Experiencing art creation as a therapeutic intervention to relieve anxiety - a case study of a university’s ceramic art course - Zhang, XiZhi; Wen, Kuohsun; Ding, Huan; Zhou, XiaoHui (Frontiers in Psychiatry, 2024)
Background University students are anxiety prone. Due to their changing their social roles, the proportion of university students with anxiety is relatively high. In this study, using the simple random sampling, we surveyed 53 university students, including sophomores, juniors, and seniors. Aims This paper examines the relationship between art creation and anxiety. Methods This study uses the Self-Assessment Anxiety Scale (SAS). The test form measures the presence and extent of their anxiety problems through a series of questions. We tested the effects of an art creation process on SAS scores and suggest best practices for course settings and teaching methods for art-related subjects. Results Art therapy intervention reduced anxiety. The most effective technique was found to be slapping the clay board during the creation process. Other actions relieved anxiety as well. Results suggest that the art creation process is an application of art therapy effective in relieving anxiety in university students. Conclusion Key actions in the process of creating art are closely related to the treatment approaches used in art therapy interventions. This has the potential to not only improve mental health, but also to promote the health and well-being of students. Implications for future research: Rapid societal changes increasing competition for employment creates work and life pressures. University students face challenges with learning, peer competition, and employment, often resulting in anxiety. A diversified curriculum can alleviate anxiety through proper curricular planning and design. Based on this, the university’s arts courses should be able to study how to improve and optimize the existing teaching and learning outcomes and can be integrated with the university’s general education curriculum planning. Through appropriate teaching content and learning methods, the courses of university general education can play a role in reducing students’ anxiety and promote physical and mental health, thus contributing to sustainable development of the society.